Baselining affects the production of deceptive narratives. Issue 1 (7th December 2020) - Tomas, Frédéric; Dodier, Olivier; Demarchi, Samuel
Abstract: Recent research shows that the quality of a baseline (i.e., the analysis of one's behavior in normal conditions) decreases when the second narrative is expected and deceitful. However, a first step would be to investigate whether the writing of a first narrative might influence the second, independently of its expectancy. In this study, we hypothesized that second narratives would be less detailed, especially if these narratives are deceptive. Participants (N = 71) were asked to narrate two consecutive truthful and deceptive narratives. The second narrative was unexpected, and the order of the narratives was counterbalanced. Results suggest a detrimental effect of deceptiveness and order on the frequency of details. Moreover, an interaction was observed, suggesting when narratives are written after a first one, the frequency of details decreases, all the more if they were deceptive. The results of this experiment are discussed from both a theoretical and an applied perspective.